Heparin affects the induction of regulatory T cells independent of anti-coagulant activity and suppresses allogeneic immune responses. (15th July 2020) - Kashiwakura, Y; Kojima, H; Kanno, Y; Hashiguchi, M; Kobata, T
Summary: Heparin is a widely used anti-coagulant that enhances anti-thrombin (AT) activity. However, heparin also suppresses immune and inflammatory responses in various rodent models and clinical trials, respectively. The mechanism by which heparin suppresses immune responses is unclear. The effect of heparin on regulatory T cells (Tregs ) in allogeneic immune responses was analysed using an acute graft- versus -host disease (aGVHD) mouse model and mixed lymphocyte reactions (MLRs). In-vitro culture systems were utilized to study the effects of heparin on Tregs . Heparin administration reduced mortality rates and increased the proportion of Tregs in the early post-transplantation period of aGVHD mice. In both murine and human MLRs, heparin increased Tregs and inhibited responder T cell proliferation. Heparin promoted functional CD4 + CD25 + forkhead box protein 3 (FoxP3) + Treg generation from naive CD4 + T cells, increased interleukin (IL)-2 production and enhanced the activation of pre-existing Tregs with IL-2. Heparin-induced Treg increases were not associated with anti-coagulant activity through AT, but required negatively charged sulphation of heparin. Importantly, N-acetyl heparin, a chemically modified heparin without anti-coagulant activity, induced Tregs and decreased mortality in aGVHD mice. Our results indicate that heparin contributes to Treg -mediated immunosuppression through IL-2 production and suggest that heparin derivatives may be useful for immunopathological control by efficient Treg induction. Graphical Abstract: